Efek Koagulan Jeruk Purut dan Jeruk Kasturi pada Kadar Air, Protein, dan Organoleptik Tahu - Septiani, Septiani; Ayunda, Hanif Muchdatul (Polyscopia, 2024)
Tofu a widely consumed and affordable food, is traditionally made using acetic acid as a coagulant. This study explores the use of kaffir lime and musk lime juice as natural coagulants due to their availability, affordability, and high acidity. A Completely Randomized Design (CRD) factorial approach was applied to assess the effects of lime type (kaffir lime and musk lime) and juice concentration (5%, 10%, and 15%) on tofu quality, focusing on water content, protein content, and organoleptic properties (color, aroma, texture, and overall acceptability). Water content decreased with higher lime concentrations, while protein content peaked at 10% musk lime juice (19.18%). Organoleptic tests showed tofu made with 10% and 15% musk lime juice was preferred over kaffir lime. Statistical analysis using ANOVA and Duncan's Multiple Range Test confirmed significant effects (p-value < 0.05). The findings suggest that musk lime juice, particularly at 10% and 15% concentrations, is an effective natural coagulant, producing tofu with better nutritional quality and consumer appeal compared to kaffir lime juice.